Laboratory study of alluvial river morphology - Khan, A. K. M. Hamidur Rahman, author; Simons, Daryl B., advisor; Schumm, Stanley, advisor; Richardson, E. V., committee member; Gessler, J., committee member (Colorado State University. Libraries, 1971)
A concrete recirculating flume 100 feet long, 24 feet wide, and about 3 feet deep was used to study the different alluvial river channel patterns. The flume was filled with sand and a series of tests were made in which discharge was varied from 0.1 to 0.3 cfs and slope was varied from 0.001 to 0.020. Four channel patterns, straight, meandering thalweg, meandering, and braided were observed in the laboratory. Straight channels developed at very flat slopes (slopes flatter than 0.0047 or 0.0026 depending on whether the flow entered the channel straight or at an angle to the axis of the flume) with very low bedload concentrations (less than 740 ppm). Meandering thalweg channels developed for slopes between 0.0023 and 0.013 and for bedload concentrations of 740 and 2180 ppm. The sinuosity was very low in these channels. Braided channels occurred at very steep slopes (slopes equal to or greater than 0.016) with high concentrations of bedload (equal to or greater than 3110 ppm). No meandering channel developed in noncohesive material. Meandering channel developed with 3% concentration of clay in the flow. Velocities were very low in straight channels (less than 0.84 fps). Meandering thalweg channels developed for velocities between 0.84 and 1.53 fps, and braided channels developed for velocities higher than 1.53 fps. Because of such variation of velocity with channel pattern, Froude number of flow, shear, and stream power was very high in a braided channel, very low in a straight channel, and intermediate in a meandering thalweg channel. Because of its low velocity, the flow in a straight channel was incapable of causing any significant erosion and as a result it maintained its original straight alignment. Meandering thalweg and braided channels developed only when the flow conditions were such that there were pronounced erosion of the channel banks. For any given bed material, thalweg meander geometry and channel geometry depend on discharge and slope or discharge and bedload concentration. Thalweg sinuosity in a meandering channel depends on discharge, slope, and bedload concentration. Width-depth ratio of channels was found to increase with bedload concentration. Laboratory experiments showed that a change in the sediment type from bedload to suspended load transforms a wide, shallow, less sinuous meandering thalweg channel into a narrow, deep, and more sinuous meandering channel. The smoothness of bed and banks, caused by the deposition of clay among the coarser materials, reduced the resistance to flow and increased the average velocity. The increased velocity caused scour of the bed. Some of the clay also deposited on the alternate bars. Continued building up of bars and scour of bed along the thalweg caused exposure of bars above water surface and the flow took place in a narrow, deep, and sinuous meandering channel.
Keywords: Channels (Hydraulic engineering)